Numerical simulation of temperature field in crack of supercritical carbon dioxide fracturing. Issue 6 (26th February 2020) - Zhou, Yi; Ni, Hongjian; Shen, Zhonghou; Wang, Wenpeng; Wang, Meishan
Abstract: Supercritical carbon dioxide (SC‐CO2 ) fracturing technology has far‐reaching application potential for unconventional resources which is beneficial to water protection and CO2 sequestration. In this paper, temperature field in the crack of SC‐CO2 fracturing which will affect flow behavior of SC‐CO2 and the carrying capacity for proppants has been studied. A generalized and pragmatic numerical method coupled with the physical properties model of CO2 and heat and mass transfer in the formation rock has been established to calculate the variations of temperature and density in the crack during fracturing. Porous medium model was used to describe the formation rock which would make the calculation more accurate. Rules of influence distance of the rock with time and injection displacement were analyzed. Distribution of temperature in XY plane is symmetrical, while temperature on the bottom wall is much less than that of the top wall in XZ plane. Decrease in injection temperature and increase in injection displacement will make the temperature of SC‐CO2 lower at the same position which is beneficial to the proppant transportation. Therefore, low injection temperature and high displacement are suggested in the application in order to make a longer proppant bed. Besides, the density of SC‐CO2 is relatively high in the formation of low rock porosity which will make the fracturing more effective. The results obtained in this paper will provide reference for SC‐CO2 fracturing design which could promote the development of this technology. Abstract : In this paper, temperature field in the crack of SC‐CO2 fracturing which will affect flow behavior of SC‐CO2 and the carrying capacity for proppants has been studied. A generalized and pragmatic numerical method coupled with the physical properties model of CO2 and heat and mass transfer in the formation rock has been established to calculate the variations of temperature and density in the crack during fracturing. The results obtained in this paper will provide reference for SC‐CO2 fracturing design which could promote the development of this technology.